Pasta with grape leaves and hops extract: Effect on quality properties, predicted glycemic index and in vitro bio-accessibility of phenolics - Bekiroglu, Hatice; Ozulku, Gorkem; Erol, Kubra Feyza; Karadag, Ayse; Sagdic, Osman (ELSEVIER, 2025)
Grape (Vitis vinifera L.) leaves and hops (Humulus lupulus L.) extract were used to enrich durum wheat pasta at 0.25 g and 0.5 g/100 g durum wheat semolina. Initially, the antioxidant capacities and phenolic compositions of extracts from grape leaves (GL) and hops were analyzed. Subsequently, the quality characteristics and predicted glycemic index (GI(predicted)) of enriched pasta were investigated. The highest cooking loss values were observed for pasta containing grape leaves (PGL) for both addition levels and pasta with 0.5% hops (PH (0.5%)). GL incorporation caused a significant reduction in water absorption value (similar to 6.5%) when compared to control pasta (CP). The highest hardness value (17.14 N) was obtained for PGL (0.5%). The GI(predicted) value was 45.54 +/- 0.27 and 52.71 +/- 0.34 for PGL (0.5%) and PH (0.5%), respectively. PGL (0.5%) and PH (0.5%) were selected for in vitro phenolic digestibility assays and sensorial evaluation due to their GI(predicted) values being lower than those achieved with 0.25% extract incorporation. Protocatechuic (5500.88 mu g/g), caffeic (5978.38 mu g/g) and vanillic acid (2717.06 mu g/g) were major phenolic acids in GL extract and they were protected during digestion. Among flavonoids, rutin was detected as 430.52 +/- 1.02 mu g/g for GL and 10274 +/- 24.08 mu g/g for hops extract while myricetin was revealed in only hops extract (367.56 +/- 2.03 mu g/g). No significant differences were observed between CP and PGL (0.5%) in terms of sensorial attributes except for odour based on a 9-point hedonic scale. Therefore, GL incorporation can be considered as a promising strategy to enrich pasta without affecting consumer satisfaction.
Keywords: Antioxidant capacity; Functional pasta; Polyphenols; Sensory properties; FUNCTIONAL-PROPERTIES; RESISTANT STARCH; VITIS-VINIFERA; DURUM-WHEAT; PROTEIN; FOOD; BIOACCESSIBILITY; DIGESTION; PROFILE; Food Science & Technology